1998
DOI: 10.1111/j.1440-1681.1998.tb02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Atherosclerosis: Vascular Protector or Villain?

Abstract: 1. Nitric oxide (NO) has important roles in physiological vasodilatation, cytotoxicity and vascular disease. Nitric oxide and prostacyclin (PGIz), both released from the endothelium, act synergistically to inhibit platelet aggregation and adhesion. These autacoids also inhibit the adhesion and migration of leucocytes and, in some arteries, they synergize in terms of vasodilatation.2. The development of atherosclerosis and hyperlipaemiaper se is accompanied by impairment of endothelium-dependent vasodilatation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 60 publications
3
28
0
4
Order By: Relevance
“…11 The present study showed that ASA treatment significantly restored the impaired vasorelaxant response to Ach only in SHRs characterized by high aortic O 2 Ϫ production, but did not modify the vasorelaxation in normotensive WKY rats. These data strongly suggest that ASA treatment improved endothelium-dependent vasorelaxant functions in SHRs mainly by its antioxidant properties, thus increasing the bioavailability of NO in response to Ach.…”
Section: Discussionmentioning
confidence: 73%
“…11 The present study showed that ASA treatment significantly restored the impaired vasorelaxant response to Ach only in SHRs characterized by high aortic O 2 Ϫ production, but did not modify the vasorelaxation in normotensive WKY rats. These data strongly suggest that ASA treatment improved endothelium-dependent vasorelaxant functions in SHRs mainly by its antioxidant properties, thus increasing the bioavailability of NO in response to Ach.…”
Section: Discussionmentioning
confidence: 73%
“…49 Superoxidemediated impairment of NO may result in vascular smooth muscle cell proliferation and migration and the expression of proinflammatory molecules, which contribute to atherosclerosis. 47,50 It is hypothesized that the elevated superoxide seen in the diabetic animals in the present study was vascular in origin, because EC-SOD is primarily vascular in nature. This hypothesis is supported by prior study showing that the apolipoprotein A1 mimetic L-4F can attenuate O 2 Ϫ production in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Production of NO in the vasculature may have beneficial effects related to the development of atherosclerosis, and these have been extensively reviewed (25)(26)(27)(28)(29)(30)(31). NO output by the constitutive form of NOS, ecNOS, expressed in endothelial cells, helps in maintaining vascular tone.…”
Section: Discussionmentioning
confidence: 99%